Reform Movement in Turkey: Changes in Geometry Content in Student Selection and Placement Examinations in Secondary Education - Incikabi, Lutfi (SAGE Publications, 2012)
This article aims to present the changes in student selection and placement examinations in secondary education by focusing on the geometry content during the postreform period. The methodology, also used by Petway (2000), includes three steps toward the aim of examining the following: technical aspects, content coverage, and examination results. Among the results of the study is that the new examinations covered more geometry content, which is distributed more evenly through the upper elementary grades than the previous ones, and that the new transition system to the secondary schools has placed more emphasis on students’ performance scores and their behavior grades at the each level of upper elementary school than the ones of the prereform period, which were mostly based on the examination results.
Keywords: 4. Education